Stent Insertion With High Intensity–Focused Ultrasound Ablation for Biliary Obstruction Caused by Pancreatic Carcinoma: A Randomized Controlled Trial. Issue 3 (17th June 2021) - Zhang, Feng-Qin; Li, Lin; Huang, Ping-Chao; Xia, Feng-Fei; Zhu, Lei; Cao, Chi
Abstract : Purpose: This study was designed to assess the clinical efficacy of stent insertion with high intensity–focused ultrasound ablation (HIFUA) in patients with malignant biliary obstruction (MBO) as a consequence of pancreatic carcinoma (PC). Materials and Methods: This was a single-center, open-label, prospective, randomized controlled trial. Consecutive patients with MBO caused by PC were randomly assigned to undergo stent insertion with or without HIFUA from June 2019 to February 2020. This study was registered at ClinicalTrials.gov (NCT03962478). Results: In total, 92 patients were enrolled in this study and assigned to the stent-only (n=46) or combined (stent+HIFUA; n=46) treatment groups. Stent insertion was associated with a 100% technical success rate. For patients in the combination treatment group, 26, 18, and 2 patients underwent 2, 3, and 4 cycles of HIFUA, respectively. A positive clinical response to HIFUA treatment was noted in 38 patients (82.6%). Stent dysfunction was detected in 9 and 15 patients in the combination and stent-only groups, respectively ( P =0.154), while median stent patency in these 2 groups was 188 and 120 days, respectively ( P <0.001). All patients died over the course of the follow-up, with median survival periods of 218 and 140 days in the combination and stent-only treatment groups, respectively ( P =0.001). The only detected predictor of prolonged survival was HIFUA treatment ( P =0.004), and there were no significant differences in complication rates between these 2 treatment groups. Conclusion: A combination of stent insertion and HIFUA can improve stent patency and overall survival in patients suffering from MBO because of PC relative to stent insertion alone.